The Garden on the Roof of the Le Corbusier Apartment: a key episode in the construction of the mature Le Corbusier’s project system - Sentkiewicz, Renata (Cuadernos de Proyectos Arquitectónicos, 2019)
Abstract The Swiss-French architect Le Corbusier created a small garden between the roof vaults of the eighth floor of the building on rue Nungesser et Coli in Paris. Designed by himself, this building housed his own home and workshop on its two upper floors, and a spiral staircase led to a small private garden. The abandonment of this garden during World War II and its rediscovery at the end of the war, transformed and given over to nature, gave Le Corbusier a new understanding of the ‘roof-garden’. He applied it to many projects in his mature work, prefiguring sensibilities integrated in similar ideas within the contemporary corpus of design methodologies.